PENGARUH KEKUASAAN KERATON YOGYAKARTA PADA SENTRA KERAJINAN TATAH SUNGGING KULIT PUCUNG YOGYAKARTA - Anwar Hidayat (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2015)
Pucung known as leather carving crafts center in Yogyakarta, who uses parchment leather material (not leather tanned) in the manufacture of production. In addition to leather puppet as flagship product, well made product variants such as lamp shades and souvenirs. The existence of this center which is located adjacent to the king's funeral, are bound up with the existence of the palace of Yogyakarta. This study aims to find out why these craft products stagnant innovation development. In examining these kind of issues, the approach of Pierre Bourdieu's habitus which include, capital, arena, distinction, and symbolic violence were used. The existence of conventional rulus (pakem) in the puppet shadow also have an impact on the development of innovative products less made Pucung crafters.